Diseño y construcción de una marmita cilíndrica con agitador y fondo esférico con rango de temperatura de 70ºc a 80ºc para producción de 50 litros de aderezos - Chacaguasay Lobato, Edgar Mauricio (2016)
The present graduation work "Design and construction of a cylindrical marmita with stirrer and spherical background with temperature range 70 °c to 80 °c production 50 l from aderezos" which was created by COMEX resolution (Resolution No. 011 -2015 Foreign Trade Committee; ANNEX A), the tariff surcharge for imports of industrial food equipment that increase the cost by 45%. This work is funded by the company Mechanical & Solutions Escorpmec S.A. who emits several major technical parameters to be respected when designing, which are explained in the second chapter. Four chapters explain the project: first chapter describes basic concepts like what is an aderezo, emulsification and also of alternatives for the selection of the marmita and theoretical foundation of jacketed container with mechanical agitation. Second chapter is about the selection of materials. The choice was made after a deep study of some alternatives. On the other hand the analysis begins with the design criteria of marmita with the following calculations and designs: design of the structure for the geared motor, tank design, design of heat transfer area, term calculation of the tank, calculation of the force exerted on the tank, design table structure and design of the agitator. One the specific objective of the project is entirely explained in chapter three. There is information about the simulation of some elements such as the tank, stirrer and structure. Finally, last chapter detail the cost that were incurred in the design, construction and commissioning of the marmita.